DAMPAK IMPLEMENTASI KURIKULUM KTSP DI SMA (STUDI KASUS PENJURUSAN KELAS XI SMAN 1 TULUNGAGUNG - Hariyoso, Hariyoso - (STKIP PGRI TULUNGAGUNG, 2019)
The new term of specialization used in curriculum 2013 (K-13) raised several issues. The specialization chose by the students in Grade X are found not linear with major they chose in Grade XI. Therefore, this research aimed to probe several questions in the following: (a) how is the procedure of declaring a major in SMAN 1 Tulungagung?; (b) how is the policy of shifting the specialization to major?; (c) what are the impacts of choosing a major in SMAN 1 Tulungagung?. In answering those questions, a descriptive qualitative method was employed in this research. It was concluded that (a) the procedure of declaring a major for students was not appropriate due to the interference of conceptions from several parties which has not reached a decision. Therefore, reconsidering the procedure in details which has been decided by the leader flown to the students and their guardians is needed. (b) Policy concerning the re-arrangement of specialization to major set aside numerous undetected problems and (c) the impacts of choosing major in SMAN 1 Tulungagung decreased students’ interest in learning particularly for social science students aside from discrimination that they faced.